The Influence of Martial Arts on Spine CT Image Morphological Structure Based on Optimized Ant Colony Algorithm - Yuhuan, Hou; Xueting, Hou; Weiyue, Wang (Computational intelligence and neuroscience, 2022)
As the second lifeline of human body, the abnormal development of its morphological structure has a great impact on people’s physical and mental health. Due to bad living habits and learning pressure, the morphological and structural development of spine in adolescents and children is abnormal to a certain extent, which can be improved by sports intervention. Therefore, this article puts forward the research on the influence of Wushu on the spinal morphological structure based on the optimization algorithm and integrates the optimization ant colony algorithm on the basis of the traditional spinal CT image segmentation method. The experimental results show that the improved CT image segmentation method based on the optimized ant colony algorithm can solve the sensitive problem of the number of clusters, improve the segmentation efficiency and quality, and provide more accurate data for the subsequent comparative experiments. At the same time, the comparative test results show that Wuqinxi Wushu can better improve the abnormal dry tilt angle, abnormal kyphosis angle, and body balance angle of teenagers, improve the activity of teenagers’ spine, and help teenagers enhance the overall health of spine.